GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 34404 species occurrences available in GBIF matching the query: TaxonKey: Reptilia Country: Madagascar. The dataset includes 34404 records from 91 constituent datasets: 105 records from UTA Herpetology. 14 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_REPTILIA. 88 records from Herpetile collection, Natural History Museum, University of Oslo. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 9 records from Herpetology. 1 records from Bird Collection of Museum and Institute of Zoology PAS. 1346 records from Museum of Comparative Zoology, Harvard University. 83 records from SMNS Herpetologie. 1 records from Reptilia Collection of Museum and Institute of Zoology PAS. 196 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 3 records from NMNH Paleobiology Specimen Records. 7 records from Queensland Museum provider for OZCAM. 1 records from SUI Vertebrate Collection. 17 records from Herpetology. 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 29 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from Collections ichtyologiques et herpétologiques (BOUM). 4 records from CUMV Reptile Collection (Arctos). 77 records from Paleobiology Database. 51 records from naturgucker. 3 records from Diveboard - Scuba diving citizen science observations. 3 records from University of California Museum of Paleontology. 14 records from SANBI: DNA Banking(1987-2011). 9 records from Lund Museum of Zoology (MZLU). 2 records from observe_tuna_bycatch_ecoscope. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 44 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 3317 records from AMNH Herpetology Collections. 93 records from Collection Herpetologie - SNSD. 14 records from The reptiles, amphibians and fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 1094 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 67 records from NRM-Herpetology. 1 records from LSUMZ Herp Tissues. 6 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 75 records from Geographically tagged INSDC sequences. 14271 records from UMMZ Herpetology Collection. 45 records from SysTax - Zoological Collections. 277 records from SuLaMa reptile survey 2013. 121 records from University of Florida Herpetology. 1159 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 23 records from Australian Museum provider for OZCAM. 5 records from LACM Vertebrate Collection. 26 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 50 records from Collection Herpetology SMF. 206 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 70 records from KUBI Herpetology Collection. 44 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 1 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 499 records from CAS Herpetology (HERP). 20 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 142 records from CM Herps Collection. 830 records from Natural History Museum (London) Collection Specimens. 5 records from Museum Victoria provider for OZCAM. 2 records from SDNHM Herpetology Collection. 149 records from Makira. 74 records from SuLaMa reptile monitoring. 411 records from SuLaMa reptile survey I 2012. 1 records from Australian National Wildlife Collection provider for OZCAM. 40 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 104 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 5 records from SMNS Palaeontological collection - Amphibians, reptiles (Palaeozoic, Mesozoic). 1 records from MPM Herpetology. 89 records from MVZ Herp Collection (Arctos). 32 records from CM Vertebrate Paleontology Collection. 1 records from ISM Herpetology Collection. 2 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 5 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 95 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 237 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 2 records from UAZ Herpetology Collection. 1 records from Northern Territory Museum and Art Gallery provider for OZCAM. 3 records from Arizona State University Amphibian and Reptile Collection. 12 records from Reptile Specimens. 1 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe).. 11 records from LSUMZ Herps Collection. 789 records from NMNH Extant Specimen and Observation Records. 1 records from Macaulay Library Audio and Video Collection. 1 records from CMC_herpetology_vouchers. 2 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 4 records from Western Australian Museum provider for OZCAM. 260 records from SuLaMa reptile survey II 2012. 18 records from Herps Specimens. 41 records from BYU Herpetology Collection. 2 records from Reptilia ZMK. 6953 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Herpetology Collection - Royal Ontario Museum. 30 records from MfN - Fossil vertebrates V. 438 records from iNaturalist Research-grade Observations. 1 records from UCM Amphibian and Reptile Collection (Arctos). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences